Bipartite begomoviruses: replication, transmission and interaction with alphasatellites - Nogueira, Angélica Maria (2018)
The genus Begomovirus includes viruses with circular single-stranded DNA, transmitted by whiteflies to dicotyledonous plants. Most New World (NW) begomoviruses have two genomic components that share a common region (CR), which contains the origin of replication recognized by the viral protein Rep to initiate replication. Natural mixed infections with two or more begomoviruses in tomato are common in the field. Previous work demonstrated that the interaction between two begomoviruses, Tomato rugose mosaic virus (ToRMV) and Tomato severe rugose virus (ToSRV), is complex, with ToRMV negatively interfering in the infectivity and accumulation of ToSRV. Interestingly, ToRMV is not widely disseminated in the field, unlike ToSRV, which predominates in tomato fields in southeastern Brazil. In addition to the effect that one begomovirus can exert on the other in the same host, NW begomoviruses have also been found in non-cultivated plants in association with alphasatellites, which depend on the helper begomovirus to cause systemic infection. The impact of a possible interaction between alphasatellites with begomoviruses in cultivated hosts such as tomato is unknown. The objectives of this thesis included: i) to verify the transmission efficiency of ToSRV and ToRMV by B. tabaci Middle East-Asia Minor 1 (BtMEAM1) and Mediterranean (BtMED) in single and mixed infections; ii) to investigate if divergent sites in the CR and Rep of these begomoviruses are involved in the negative interference that ToRMV exerts on the replication of ToSRV; iii) to verify if the alphasatellite Euphorbia yellow mosaic alphasatellite (EuYMA) is capable of interacting with two tomato-infecting begomoviruses, Tomato yellow spot virus (ToYSV) and ToSRV. For the first objective, corresponding to the first chapter, plants that were biolistically inoculated with each virus in single and mixed infections were used as inoculum sources. ToSRV was transmitted with the same efficiency in relation to ToRMV by BtMEAM1 and at higher rates by BtMED in single infections. However, ToRMV was transmitted more efficiently than ToSRV in mixed infections, suggesting that this preferential transmission of ToRMV over ToSRV may be related to replication. For the second objective, corresponding to the second chapter, ToSRV DNA-A mutants containing the same nucleotides of ToRMV DNA-A at the divergent positions in the CR and within the IRD (iteron-related domain) of the Rep gene were constructed. In mixed inoculation with ToRMV, high accumulation of ToSRV DNA-A containing mutations in the CR was observed (as compared to wild-type ToSRV), suggesting that the mutated CR sites serve as specific recognition sites for Rep binding, increasing viral replication and viral DNA accumulation. For the third objective, corresponding to the third chapter, tomato and Nicotiana benthamiana plants were biolistically inoculated with ToYSV and ToSRV in the presence or absence of the alphasatellite. Interaction of the two begomoviruses with EuYMA was demonstrated, and shown to be associated the increased symptom severity. The association of EuYMA with ToYSV was less efficient in tomato than in N. benthamiana, while that between ToSRV and EuYMA was similar in both hosts, indicating differences in the interaction between the alphasatellite and different tomato- infecting begomoviruses., The results of this study provide new information that increases the understanding of virus, DNA satellite, vector and host interactions that contribute to the adaptation and predominance of begomoviruses in the field.